Resettlement of Northern Muslims: A Challenge for Sustainable Post-War Development and Reconciliation in Sri Lanka - Yusoff, Mohammad Agus; Sarjoon, Athambawa; Mohd. Zain, Zawiyah (Medwell Journal, 2018)
This study drew on important insights from a quarter-century history of forcefully evicted Muslims in Sri Lanka’s northern province by examining the nature of their displaced life and their permanent resettlement in their traditional villages, particularly in the post-civil war context. Reviewing the literature and primary sources, this paper argues that the forceful eviction of northern Muslims was unfortunate and the persistent sidetracking of their permanent resettlement violated their right to live in their traditional villages. Successive governments have failed to propose a sustainable mechanism to resettle these Muslims as part of the resettlement plans. Post-war resettlement initiatives hardly considered the permanent resettlement of these Muslims in their traditional villages. In addition, the issue of resettling northern Muslims became highly contested due to lack of proper policies and plans of the government authorities, as well as moral and institutional support from the Tamil community and their polity, opposition, and criticisms from the Sinhalese-Buddhist nationalist forces, and fragmentation within Muslim politics, together with the protracted nature of the displacement. This study suggested that the continued neglect of their resettlement would challenge the sustainability of post-war development and ethnic reconciliation in Sri Lanka